Water Pollution Hazards and Toxicity Caused by Textile Industries Effluent - Ghulam Mujtaba; Noor Muhammad; Qaim Shah; Murad Khan; Nabeel K. Abbood (Journal of ICT, Design, Engineering and Technological Science, 2023)
Water pollution is a serious environmental problem that endangers both human health and ecosystems. Due to its heavy use of chemicals and water-intensive processes, the textile industry is one of the biggest contributors to water pollution. Water contamination occurs when effluent from textile manufacturing facilities enters water bodies including rivers, lakes, and groundwater after being improperly or not at all treated. These contaminants may have negative impacts on aquatic life, including reducing their capacity for reproduction, upsetting ecosystems, and even killing aquatic organisms. Furthermore, anyone who uses contaminated water sources for agriculture, pleasure, or drinking can face major health hazards. Heavy metals, volatile organic compounds (VOCs), surfactants, and other harmful substances are some of the pollutants identified in effluent from the textile industry. To reduce water pollution, this abstract emphasizes the critical necessity for sustainable practices in the textile industry for which different investigatory experimental performances were done to highlight and resolve the issue. Chloride content, turbidity and hardness tests were done to evaluate the hazards that are caused by the water pollution. It is possible to lessen the environmental impact of textile production and protect water resources for future generations by implementing efficient pollution prevention measures and adopting cleaner production techniques.